2023
DOI: 10.1021/acs.langmuir.3c00711
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of AlH3 Crystals by the Coating of Hydrophobic PFPE and Resulted Reactivity with Ammonium Perchlorate

Abstract: Aluminum hydride (AlH 3 ) is a promising fuel component of solid propellant, but its stabilization is still challenging. Herein, surface functionalization of hydrophobic perfluoropolyether (PFPE) followed by ammonium perchlorate (AP) coating has been implemented. In particular, AlH 3 @PFPE@xAP (x = 10, 30, 50, or 64.21%) composites (AHFPs) were prepared by a spraydrying technique. The PFPE-functionalized AlH 3 with a hydrophobic surface shows an increased water contact angle (WCA) from 51.87°to 113.54°. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Moreover, they have impressive thermal and oxidative stability. Our previous study also indicated that PFPE-functionalized AlH 3 showed a significant increase in both water contact angle and energy output . However, there have been limited reports on research conducted on the inclusion of stabilized AlH 3 in solid propellants.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, they have impressive thermal and oxidative stability. Our previous study also indicated that PFPE-functionalized AlH 3 showed a significant increase in both water contact angle and energy output . However, there have been limited reports on research conducted on the inclusion of stabilized AlH 3 in solid propellants.…”
Section: Introductionmentioning
confidence: 76%
“…The corresponding peak temperatures of AP decomposition in pure AlH 3 -based propellants (SP11) are 319.6 and 363.3 °C, and the exothermic peak temperature is 367.5 °C, which is reduced by 4.1, 16.8, and 14.5 °C, respectively. These results indicate that the hydrogen of AlH 3 can promote the rapid decomposition of AP, mainly because the H 2 produced by the decomposition can take away the material on the surface of AP to promote the decomposition . Upon comparing the thermal decomposition process of propellants containing AHAPs (SP13) and AHAPs-F (SP14) with that of the mechanically mixed component propellant (SP12), it was observed that the low- and high-temperature decomposition peak temperatures of AP in SP13 increased by 6.2 and 3.8 °C, respectively, indicating that the stability of AP can be slightly enhanced after embedding Al and AP.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation